Postgraduate Psychology Students’ Perceptions of Mental Wellbeing and Mental Health Literacy: A Preliminary Mixed-Method Case Study - Helen Payne; Kristen Leslie (Education Sciences)
This preliminary study aimed to explore postgraduate students’ perceptions of mental wellbeing and mental health literacy at a university in the East of England. Due to government widening participation initiatives, more students from minority groups are attending universities, most of which have expanded their wellbeing support offers to students through dedicated Student Wellbeing Services and student success teams. This study employed mixed methods with two stages. The first stage, quantitative data collection, employed an online survey (designed by the first author), analysed by Qualtrics with resulting data used to select themes for the second stage, a focus group discussion, analysed by inductive thematic analysis. Five themes and eight sub-themes were identified: 1. Expectations: The university and students. 2. Judgement: Personal perceptions and mental health stigma. 3. Stress: University disorganisation and how stress feels. 4. International Students: Difficulties with studying and healthcare. 5. The National Health Service. The data shed further light on students’ levels of understanding of mental wellbeing (mental health literacy), providing important information for HE policymaking on students’ expectations of support for mental wellbeing. Participants advocated for more promotion of real student experiences of dealing with mental health issues and clearer signposting of support services to further tackle stigma.